2021
DOI: 10.1111/1759-7714.14238
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00460: Function and mechanism in human cancer

Abstract: Long non‐coding RNAs (LncRNAs), which are more than 200 nucleotides in length and with limited protein‐coding potential, play vital roles in the pathogenesis, tumorigenesis, and angiogenesis of cancers. Aberrant expression of lncRNAs has been detected in various carcinomas and may be correlated with oncogenesis by affecting related genes expression. Recently, an increasing number of studies have reported on long intergenic non‐protein coding RNA 460 (LINC00460) in human tumor fields. LINC00460 is upregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…6b. According to the results of differentially expressed analysis and relevant literature [14][15][16][17] , LINC00460 and LINC00551 were www.nature.com/scientificreports/ selected for further validation. LINC00460 expression was substantially higher in ccRCC (logFC = 5.039969, P = 1.74e−19), however, LINC00551 was downregulated in ccRCC (logFC = − 3.51939, P = 1.62e−36).…”
Section: Development and Verification Of Prognosis Flpsmentioning
confidence: 99%
“…6b. According to the results of differentially expressed analysis and relevant literature [14][15][16][17] , LINC00460 and LINC00551 were www.nature.com/scientificreports/ selected for further validation. LINC00460 expression was substantially higher in ccRCC (logFC = 5.039969, P = 1.74e−19), however, LINC00551 was downregulated in ccRCC (logFC = − 3.51939, P = 1.62e−36).…”
Section: Development and Verification Of Prognosis Flpsmentioning
confidence: 99%
“…It has been reported that LINC00460 is increased in diverse cancer tissues and is associated with clinicopathological characteristics of cancer patients. 11 For example, the expression levels of LINC00460 were increased in colorectal cancer tissues and colorectal cancer patients with high LINC00460 expression showed poor 5-year overall survival and disease-free survival. 26 In prostate cancer, LINC00460 was reported to be increased in cancer tissues, and high LINC00460 expression was correlative to tumor size and high Gleason score.…”
Section: Discussionmentioning
confidence: 95%
“… 7 10 Long intergenic noncoding RNA 460 (LINC00460) is located in the chr13q33.2 region and has been demonstrated to be increased in many types of solid tumors, such as colorectal cancer, hepatocellular carcinoma, lung cancer, and renal cell carcinoma. 11 The levels of LINC00460 were upregulated in the breast cancer tissues and positively associated with lymphatic metastasis and poor overall survival of patients with breast cancer. 12 Moreover, LINC00460 was identified as an oncogenic gene and promoted breast cancer progression through the miR-489-5p/Fibroblast Growth Factor 7 (FGF7)/AKT axis.…”
Section: Introductionmentioning
confidence: 96%
“…Aberrant expression of lncRNA is a common biological phenomenon and is closely related to the prognosis of cancers ( 37 ). LINC00460 is widely and highly expressed in human cancers and acts as a potential oncogene, which is a potential biomarker for cancer diagnosis, prognosis, and therapy ( 38 ). The correlation between lncRNAs and immune cells suggests that LINC00460 was highly and positively associated with immune status, indicating it might be the essential biomarker for the signature.…”
Section: Discussionmentioning
confidence: 99%